Le texte et la formation des romanistes au Français sur Objectifs Spécifiques - Gajewska, Elżbieta; Sowa, Magdalena (2023)
The study of philology (including Romance studies) has opened up very widely to specialized communication, introducing LSP classes into the curricula. The basis of language content programming for professional purposes is essentially a text (specialized text). Despite its many definitions, it is necessary, first of all, to pay attention to those that treat the text as a material manifestation of discourse and genre, and use it to conduct an analysis of the communicative and linguistic needs of learners. This article discusses the problem of the (in)presence of specialized text in philological education preparing for professional activity. Based on the analysis of philological study programs in Poland, it can be seen that they use text to varying degrees and extents in the teaching of various LSP. Text is certainly part of the names of the subjects (especially translation classes), but to a small extent it is possible to notice its presence in the analysis of needs and conceptualization of content in terms of communicative practices in the target work environment.
Keywords: philology; curriculum; teaching language for professional purposes; text; specialized text